Effects of primer excess on marginal adaptation, nanoleakage and bond strength of adhesive systems after aging - Suelem Chasse Barreto; Isabel Ferreira Barbosa; Gisele Damiana da Silveira Pereira; Carlos Tadeu dos Santos Dias; Luís Alexandre Maffei Sartini Paulillo (Universidade Estadual de Campinas, 2019)
There is no consensus about the amount of primer inserted into the cavity. Aim: This study aimed to evaluate the effects of the amount of primer used on dentin microtensile bond strength (µTBs), nanoleakage and marginal sealing, following thermomechanical aging. Methods: 48 human third molars were selected and a box-shaped class I cavity was constructed to maintain enamel margins. Teeth were randomly assigned to 6 experimental groups (n=8). For the bonding protocols of the restorative procedure, two adhesive systems were used: three-step etch-and-rinse and two-step self-etch. Epoxy resin replicas of the occlusal surface were made, and the specimens were submitted to thermomechanical aging. Newer replicas were obtained after thermomechanical aging, and marginal adaptation was observed using SEM. To obtain sections (0.7 x 0.7 mm) for testing at a tension of 0.5 mm/min, teeth were serially sectioned in the buccallingual direction, parallel to the occlusal surface. Failure mode was then obtained. For nanoleakage evaluation, one section of each tooth was immersed in AgNO3 and evaluated using SEM. The μTBs data were submitted to a two-way ANOVA and Tukey's test (α= 0.05) Results: One drop of primer promoted higher µTBs than two or three drops. Besides, the three-step etch-and-rinse promoted greater μTBs (19.78) than the two-step self-etch adhesive (12.23). The increase in the amount of primer was directly proportional to the increase of infiltration. All groups exhibited more gaps after thermomechanical aging. Conclusion: Using an excess of primer is not recommended because it reduces the μTBs and forms an unsatisfactory hybrid layer.